Steroid hormone receptor regulation of neuronal pruning and outgrowth in the Drosophila central nervous system - Brown, Heather L. D (My University, 2007)
During metamorphosis, the reorganization of the CNS of Drosophila melanogaster occurs via death of most larval neurons, remodeling of surviving larval neurons, and production of de novo adult neurons. This restructuring is driven by the steroid hormone ecdysone, and its receptor, EcR. In this study, I examined the role of EcR in regulating the development of both remodeling and de novo neurons within the CNS. I expressed various EcR constructs in the remodeling Thoracic-ventral (Tv) neurons and examined both pruning and outgrowth. Axons of these neurons prune their larval arbors early in metamorphosis and a larger, more extensive adult arbor is established via branch outgrowth. Both knockdown of total EcR and expression of EcR dominant negative constructs resulted in pruning defects of larval axons, but variable effects on outgrowth were seen depending on the construct expressed, When the blend of wild type EcR isoforms was altered, the timing of remodeling phases was changed. Pruning was accelerated by overexpression of the EcR-B isoforms. Overexpression of EcR-B2 resulted in precocious outgrowth of the Tv axons, possibly indicating a derepressive role for this isoform. I also examined the function of EcR in development of de novo neurons. When EcR-DN was expressed in clones of the adult-specific lineages, neuroblasts were retained longer in clones expressing EcR-DN. There was no alteration in the lineages' primary, initial projection. We did see defects in secondary arbors of both central and peripheral projections, which varied across the lineages and included clumping and cohesion of fine branches, misrouting, smaller arbors and some defasciculation.The results from this study are consistent with the role of EcR activation versus derepression for successive phases of neuronal remodeling, and suggest that functional ecdysone receptor is necessary for some, but not all, remodeling events. Additionally, they point to previously unknown roles for the EcR isoforms in driving outgrowth in remodeling neurons. Finally, the data from the adult-specific neuron lineages indicate that EcR plays a lesser role in regulating their outgrowth than in neurons that remodel.
Thesis (Ph. D.)--University of Washington, 2007.
Keywords: Theses--Molecular and cellular biology